Soil and Water Conservation in the Himalayan region: must to increase and stabilize crop yields - ACHARYA, C. L. (Journal of Soil and Water Conservation, 2021)
The Himalaya accounts for approximately 18% of India’s land area, extending for about 2500 km, stretching from Kashmir in the west to Arunachal Pradesh in the east. The enormous altitudinal variations within short distances give rise to the corresponding climatic variations of large amplitude and together with the marked changes in humidity from east to west, result in a diversity of habitats and biota unsurpassed by any other mountain range of the world. The Himalaya also forms the origin of all north Indian rivers and thereby influences well-being of the vast plain lands of the country. The ecological security of the Himalayas is not only vital for the welfare of the hill people and their children but also for the food security of India. The destiny of nearly 40 % of our population inhabiting the Gangetic plains depends on the management of the Himalayan hydrologic estate. One of the urgent tasks facing us is the conservation and wise use of this extensive hydrologic estate, spread over an area of about 6,50, 000 sq.km. Thus, the future of agriculture in the Indo-Gangetic plains, a major food basket region of India, will be determined by what we do or do not do in the Himalayas today. The watershed management and development program for the effective soil, land and water management in the country should begin from Himalayan region downward rather than the other way. The result of so far neglect and mismanagement of the natural resources in the Himalayan region has been witnessed in the recent past in many of the places due to ecological disturbances in the Himalayas which has threatened not only this region but have shown catastrophic long-term impacts on the plains as well and consequently the whole of the country. The maximum impact of the destruction of land, water and biomass resources falls on women of the region who play the major role in the collection of fuel, fodder and water. Since the problems of the entire Himalayan region cannot be generalized as these are location specific, there is a need for a land and water use strategy for each compact agro-ecological zone with a view to promoting conservation, restoration and sustainable utilization of natural resources.